2007
DOI: 10.1128/jb.00201-07
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis SigF Regulates Genes Encoding Cell Wall-Associated Proteins and Directly Regulates the Transcriptional Regulatory Gene phoY1

Abstract: Mycobacterium tuberculosisSigF is homologous to stress response and sporulation sigma factors in many bacteria. Consistent with a possible role in mycobacterial survival under stress conditions, M. tuberculosis sigF is strongly induced within cultured human macrophages and upon nutrient starvation, and SigF has been implicated in M. tuberculosis entry into stationary phase. On the other hand, SigF appears to contribute to the immune pathology of tuberculosis (TB), and a sigF-deficient mutant has altered cell m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 36 publications
3
55
2
2
Order By: Relevance
“…In contrast to our previous findings (Dheenadhayalan et al, 2006b), Williams et al (2007) have shown that expression of M. tuberculosis PE_PGRS 26 is significantly upregulated following induction of sigma factor F, which may help mycobacteria survive under stressful environmental conditions. The differences in host cell responses observed in the present studies using PE_PGRS 16 compared to PE_PGRS 33 and PE_PGRS 26 suggest that regulated expression of different PE_PGRS proteins by M. tuberculosis could affect the fate of the mycobacterial pathogen as well as the response by the host to infection.…”
Section: Vaccine Groupcontrasting
confidence: 55%
“…In contrast to our previous findings (Dheenadhayalan et al, 2006b), Williams et al (2007) have shown that expression of M. tuberculosis PE_PGRS 26 is significantly upregulated following induction of sigma factor F, which may help mycobacteria survive under stressful environmental conditions. The differences in host cell responses observed in the present studies using PE_PGRS 16 compared to PE_PGRS 33 and PE_PGRS 26 suggest that regulated expression of different PE_PGRS proteins by M. tuberculosis could affect the fate of the mycobacterial pathogen as well as the response by the host to infection.…”
Section: Vaccine Groupcontrasting
confidence: 55%
“…SigF did not appear to be required for survival of stress conditions such as heat and cold shock or long-term stationary-phase survival (Chen et al, 2000). In fact, a recent study using both deletion as well as overexpression of sigF in M. tuberculosis suggested that SigF has a role in the regulation of the structure and function of the mycobacterial cell wall, rather than being a general stressresponse sigma factor (Williams et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…No induction compared to unexposed control cells was observed under these conditions (data not shown), confirming that the observed induction of rsbW-lacZ was indeed due to exposure to D-cycloserine. In M. tuberculosis, SigF appears to have a role in the regulation of genes involved in cell envelope biosynthesis (Geiman et al, 2004;Williams et al, 2007). It may therefore be that cell wall stress, e.g.…”
mentioning
confidence: 99%
“…However, it has since become clear that SigF is well conserved among mycobacteria (30,31) and regulates more than just virulence. While SigF is related to stress response and sporulation sigma factors in other bacteria (8), its role as a stress and stationary-phase sigma factor in M. tuberculosis is under debate (40).…”
mentioning
confidence: 99%
“…Loss of the alternative sigma factor SigF decreased the virulence of M. tuberculosis in mice (5) and disease-associated tissue damage in mice (13) as well as guinea pigs (20). Loss of SigF also leads to an altered cell wall composition due to a lack of virulence-related sulfolipids (13), and overexpression of sigF has been shown to affect the regulation of other cell wall-associated proteins involved in host-pathogen interaction (40).…”
mentioning
confidence: 99%